Divergent consumer preferences and visions for cooking and heating technologies in the United Kingdom: make our homes clean, safe, warm and smart! - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Elsevier, 2023)
Decarbonising the global housing stock is imperative for reaching climate change targets. In the United Kingdom, hydrogen is currently being tested as a replacement fuel for natural gas, which could be used to supply low-carbon energy to parts of the country. Transitioning the residential sector towards a net-zero future will call for an inclusive understanding of consumer preferences for emerging technologies. In response, this paper explores consumer attitudes towards domestic cooking and heating technologies, and energy appliances of the future, which could include a role for hydrogen hobs and boilers in UK homes. To access qualitative evidence on this topic, we conducted ten online focus groups (N = 58) with members of the UK public between February and April 2022. The study finds that existing gas users wish to preserve the best features of gas cooking, such as speed, responsiveness and controllability, but also desire the potential safety and aesthetic benefits of electric systems, principally induction hobs. Meanwhile, future heating systems should ensure thermal comfort, ease of use, energy efficiency and smart performance, while providing space savings and noise reduction, alongside demonstrable green benefits. Mixed-methods multigroup analysis suggests divergence between support levels for hydrogen homes, which implies a degree of consumer heterogeneity. Foremost, we find that domestic hydrogen acceptance is positively associated with interest and engagement with renewable energy and fuel poverty pressures. We conclude that internalising the perspectives of consumers is critical to enabling constructive socio-technical imaginaries for low-carbon domestic energy futures.
Keywords: Domestic energy futures; Hydrogen transition; Focus groups; Heat decarbonization; Low-carbon-cooking; Socio-technical imaginaries